Highly plastic chromosomal organization in Salmonella typhi. - Liu, S L (1996)
Gene order in the chromosomes of Escherichia coli K-12 and Salmonella typhimurium LT2, and in many other species of Salmonella, is strongly conserved, even though the genera diverged about 160 million years ago. However, partial digestion of chromosomal DNA of Salmonella typhi, the causal organism of typhoid fever, with the endonuclease I-CeuI followed by separation of the DNA fragments by pulsed-field gel electrophoresis showed that the chromosomes of independent wild-type isolates of S. typhi are rearranged due to homologous recombination between the seven rrn genes that code for ribosomal RNA. The order of genes within the I-CeuI fragments is largely conserved, but the order of the fragments on the chromosome is rearranged. Twenty-one different orders of the I-CeuI fragments were detected among the 127 wild-type strains we examined. Duplications and deletions were not found, but transpositions and inversions were common. Transpositions of I-CeuI fragments into sites that do not change their distance from the origin of replication (oriC) are frequently detected among the wild-type strains, but transpositions that move the fragments much further from oriC were rare. This supports the gene dosage hypothesis that genes at different distances from oriC have different gene dosages and, hence, different gene expression, and that during evolution genes become adapted to their specific location; thus, cells with changes in gene location due to transpositions may be less fit. Therefore, gene dosage may be one of the forces that conserves gene order, although its effects seem less strong in S. typhi than in other enteric bacteria. However, both the gene dosage and the genomic balance hypotheses, the latter of which states that the origin (oriC) and terminus (TER) of replication must be separated by 180 degrees C, need further investigation.